Dis-implementation of the Islamic Family Law in Fulfilling the Rights of Ex-Wives After Divorce in Indonesia - Rahmawati, Rahmawati; Budiman, Budiman; Saka, Putri Ananda; binti Abdul Manaf, Noerhoneydayatie; Sunuwati, Sunuwati (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study seeks to examine the modalities of disimplementation of the Islamic family law in addressing the rights of ex-wives post-divorce. The study is crucial as the disimplementation of the law can lead to injustice, legal confusion, and dissatisfaction for the people that the law is intended to protect. This case study examines the disimplementation of ex-wives' rights post-divorce within the religious courts of Pinrang, Sidrap, Tangerang, and Pariaman in Indonesia. Data were collected through interviews and document analysis. The data analysis employed a three-stage interpretative method: restatement, description, and interpretation. The findings reveal that the disimplementation of the Islamic family law regarding the rights of ex-wives post-divorce arises from three factors: firstly, the ex-husband's failure to fulfill his obligations towards his ex-wife's rights. Secondly, the presence of a complex execution process for realizing the wife's rights necessitates substantial financial resources (bureaucracy). Third, deficiencies in law enforcement include the complexities of the legal process for victims (ex-wives), inadequate penalties, and limited legal literacy among ex-wives concerning their rights. The inability to uphold these rights has resulted in economic, social, and psychological damages for ex-wives. This disimplementation is theoretically attributed to inadequate law enforcement, alongside the influences of law enforcement agents, culture, and societal dysfunction.